Spontaneous remission of the mandibular nerve paresthesia: a case report - Martins, Ronald Jefferson; Belila, Naiana de Melo; Kato, Mayumi Domingues; Garbin, Cléa Adas Saliba (ARCHIVES OF HEALTH INVESTIGATION, 2018)
Introduction: Paresthesia is usually characterized by a transient loss of sensitivity in the area covered by the affected nerve. Different causes may lead to this occurrence; among them, the injury of nerve structures during the extraction of third molars. The sensitivity recovery depends on the regeneration of the nerve fibers, and in most cases it occurs spontaneously. In some situations, there is a need for a more invasive and expensive treatments to the patient. Objective: The aim of this study was to evaluate the spontaneous remission of the inferior alveolar nerve paresthesia. Case report: We studied a 34 year-old patient, white, male, which presented paresthesia of the inferior alveolar nerve after extraction of the lower right third molar. We chose to wait for the spontaneous return of the sensitivity, which occurred between the first and second postoperative month. Conclusion: The complete recovery of the sensitivity does not occur in all cases, even with the recommended treatments. So the best way to deal with paresthesia is prevention, where the dentist must perform the correct diagnosis with the aid of the necessary additional tests; besides having skill and dexterity in handling the instruments, so that the surgery would be performed safely and without any complications for the patient. Descriptors: Paresthesia; Remission, Spontaneous; Mandibular Nerve.